1994
DOI: 10.1152/jappl.1994.76.4.1719
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneity of pulmonary ventilation during sustained microgravity as determined by single-breath washouts

Abstract: Gravity is known to cause inhomogeneity of ventilation. Nongravitational factors are also recognized, but their relative contribution is not understood. We therefore studied ventilatory inhomogeneity during sustained microgravity during the 9-day flight of Spacelab SLS-1. All seven crew members performed single-breath nitrogen washouts. They inspired a vital capacity breath of 100% oxygen with a bolus of argon at the start of inspiration, and the inspiratory and expiratory flow rates were controlled at 0.5 l/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
86
2
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 0 publications
17
86
2
2
Order By: Relevance
“…Their model is an electric circuit model consisting of three compartments without gravity effect. However, it is known that gravity effect is necessary for cardiogenic oscillation, as shown by Guy's microgravity experiments [21]. Our present simulation is consistent with their experiments because cardiogenic oscillation is generated by intrapulmonary inhomogeneity of the nitrogen concentration caused by gravity effect in our model.…”
Section: Validity Of the Lung Deformation Modelsupporting
confidence: 90%
“…Their model is an electric circuit model consisting of three compartments without gravity effect. However, it is known that gravity effect is necessary for cardiogenic oscillation, as shown by Guy's microgravity experiments [21]. Our present simulation is consistent with their experiments because cardiogenic oscillation is generated by intrapulmonary inhomogeneity of the nitrogen concentration caused by gravity effect in our model.…”
Section: Validity Of the Lung Deformation Modelsupporting
confidence: 90%
“…All tests were performed on a system identical to that previously used to study ventilation inhomogeneity in G studies (20,25,40,43). Briefly, the system comprises of a bag-in-box system with separate bags for inspired and expired gases.…”
Section: Methodsmentioning
confidence: 99%
“…These data were converted to our standard laboratory format, by using a personal desktop computer, and analyzed with the same techniques applied to data previously obtained during G (20,38,40).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the classical SBW manoeuvre involved inspiration of the test gases over a vital capacity (VC) manoeuvre, and microgravity experiments performed in the meantime have confirmed that the phase-III slope resulting from the classical SBW test is in fact a mixture of small-and large-scale ventilation inhomogeneities, partly dependent on gravity and airway closure [26,27]. By contrast, a modified SBW test starting the inspiration from functional residual capacity (FRC) has been shown to be less affected by confounding effects, such as gravity [28].…”
mentioning
confidence: 99%